2012
DOI: 10.1152/ajpheart.00327.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mesenteric endothelial function of streptozotocin-induced diabetic rats: a shift in the relative importance of EDRFs

Abstract: Rahimian R. Sex differences in mesenteric endothelial function of streptozotocin-induced diabetic rats: a shift in the relative importance of EDRFs. Am J Physiol Heart Circ Physiol 303: H1183-H1198, 2012. First published September 14, 2012 doi:10.1152 doi:10. /ajpheart.00327.2012 studies suggest that diabetes affects male and female vascular beds differently. However, the mechanisms underlying the interaction of sex and diabetes remain to be investigated. This study investigates whether there are 1) sex differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
53
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 92 publications
(116 reference statements)
16
53
0
2
Order By: Relevance
“…The data reveal profound differences in the effects of cardiometabolic risk factors on the components of endothelial dilation in females versus males. In males (Figure 4), in the absence of risk factors, both eNOS and EDH contribute to vasodilation, with NOS contributing a greater proportion of mesenteric vasodilatory function than EDH (Figure 4A and 4D), consistent with prior studies 14, 15. Exposure of male mice to obesity, with or without hyperlipidemia, resulted in profound impairment in eNOS‐mediated relaxation of resistance vessels.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The data reveal profound differences in the effects of cardiometabolic risk factors on the components of endothelial dilation in females versus males. In males (Figure 4), in the absence of risk factors, both eNOS and EDH contribute to vasodilation, with NOS contributing a greater proportion of mesenteric vasodilatory function than EDH (Figure 4A and 4D), consistent with prior studies 14, 15. Exposure of male mice to obesity, with or without hyperlipidemia, resulted in profound impairment in eNOS‐mediated relaxation of resistance vessels.…”
Section: Resultssupporting
confidence: 81%
“…Hydrogen peroxide (H 2 O 2 ) is an additional vasodilator that activates potassium channels to contribute to EDH 12, 13. Sex differences have been described in the relative contribution of these endothelium‐derived relaxing factors to resistance vessel function in rodent models 14, 15. However, how these components are modulated in resistance vessels in response to cardiometabolic risk factors and whether there are sex differences in those responses have not been directly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EET was more effective in female mice than in male mice (33). Another study showed that the female hormone estrogen has anti-inflammatory effects (20) and increases the expression of EET (10).…”
Section: Discussionmentioning
confidence: 97%
“…In clinical characteristics, the ratio of HT and current smoking of men was significantly higher than that of women (73 vs. 54.5%, P ϭ (12) reported that the spasm group has a high ratio of men, smokers, and HT. Spasm is defined by the presence of epicardial vasodilation; herein, the definition of CMVD was completely different, but it is reported that men have more influence of NO than women in vascular tone (17,24,33). Thus it is possible that the factors of decreasing NO as HT and smoking are predicted as incidence of CMVD, especially in men.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports including our previous studies have shown that acute exposure of blood vessels to high glucose impairs EDV to ACh (Goel et al 2008;Goel et al 2007). Impaired EDV has been also reported in experimental models of diabetes (De Vriese et al 2000;Johnstone et al 1993;Zhang et al 2012). However, there are also reports demonstrating an enhanced EDV in diabetes (Bhardwaj and Moore 1988;Shen et al 2003), and alterations in EDV are dependent on the duration of the diabetic state (Clarkson et al 1996;Pieper 1999).…”
Section: Introductionmentioning
confidence: 84%